IMPLEMENTATION OF REGULATION OF THE MINISTER OF MANPOWER NUMBER 6 OF 2020 CONCERNING THE IMPLEMENTATION OF DOMESTIC APPRECIATION IN KARAWANG, WEST JAVA - Listiono listiono; Deny Guntara; Muhamad Abas (Universitas Muhammadiyah Tangerang, 2023)
Indonesia is a constitutional state with a rule of law that is very useful for society, and the law must provide benefits and goals for humanity. In general, employment in apprenticeship practices results in that there are still many companies that do not give an allowance amount. In the corporate world, labor is one of the most significant expenses in the corporate world, so in this case, if the work (interns) is not paid, it can benefit the company. Meanwhile, interns also have other needs in their daily activities. This can harm both parties, namely apprentices (apprentices) and the company. The problem is how the apprenticeship program is implemented in Indonesia in terms of the Minister of Manpower Regulation Number 6 of 2020 concerning the Implementation of Domestic Apprenticeships and what are the inhibiting factors in implementing the apprenticeship program in Indonesia. The research method is qualitative, with the approach used in this study being normative juridical. The research results on implementing the Apprenticeship Program in Karawang in terms of the Minister of Manpower Regulation Number 6 of 2020 concerning the performance of Domestic Apprenticeships have been running according to the rules contained in the regulation. In practice, there are still many companies placing apprentices that are not under their competence or expertise, that have been carried out so that it is not in line with the objectives of the Organization of Domestic Apprenticeships. There are lacks that the specialists found in every part of adequacy, and these elements show that the execution of the Guideline minister of workforce regulations of the Republic of Indonesia Number 6 of 2020 concerning the Execution of Homegrown Apprenticeships concerning the privileges of student members is as yet not successfully carried out in the field.Keywords: Implementation, Effectiveness, Apprenticeship